An early Aurignacian arrival in southwestern Europe. - Cortés-Sánchez, Miguel; Jiménez-Espejo, Francisco; Simón-Vallejo, M. Dolores; Stringer, Chris; Lozano-Francisco, María del Carmen; García-Alix, Antonio; Vera-Peláez, José L.; Odriozola, Carlos; Riquelme-Cantal, José A.; Parrilla Giráldez, Rubén; Maestro González, Adolfo; Ohkouchi, Naohiko; et al. (Nature Publishing Group UK, 2019)
Westernmost Europe constitutes a key location in determining the timing of the replacement of Neanderthals by anatomically modern humans (AMHs). In this study, the replacement of late Mousterian industries by Aurignacian ones at the site of Bajondillo Cave (Málaga, southern Spain) is reported. On the basis of Bayesian analyses, a total of 26 radiocarbon dates, including 17 new ones, show that replacement at Bajondillo took place in the millennia centring on ~45–43 calibrated thousand years before the present (cal ka bp)—well before the onset of Heinrich event 4 (~40.2–38.3 cal ka bp). These dates indicate that the arrival of AMHs at the southernmost tip of Iberia was essentially synchronous with that recorded in other regions of Europe, and significantly increases the areal expansion reached by early AMHs at that time. In agreement with human dispersal scenarios on other continents, such rapid expansion points to coastal corridors as favoured routes for early AMH. The new radiocarbon dates align Iberian chronologies with AMH dispersal patterns in Eurasia.
An early Aurignacian arrival in southwestern Europe
Keywords: Hombre de Neandertal; Prehistoria - Europa meridional; Aurignacian; Europe; Neanderthals; Bajondillo Cave